(untitled) (Journal of Economic Research & Business Administration, 2016)
International finances development of that passes ahead the height of world production and export became the main motive body of internation alization of world economy in the last decades. Exactly meeting streams of direct investments, diversification, expansion and integration of interna tional financial markets, showed out a world economy on the qualitatively new level of internationalization – globalization. Kazakhstan became one of the first victims of world financial crisis. On the Kazakhstan stock exchange a sharp fall in the prices leading banks’ stock was found. Banks were forced to decrease volumes of crediting. Impossibility of getting a credit became a reason of slump in consumprion activity of population. But not only population. A Businessassociation shortened the activity also. Plenty of medium and small banks went bank rupt as a result. And withstanding banks went on toughening in terms of delivery of consumer credits.